A NOVEL APPROACH TO STUTTERED SPEECH CORRECTION - Alim Sabur Ajibola; Nahrul Khair bin Alang Md. Rashid; Wahju Sediono; Nik Nur Wahidah Nik Hashim (Jurnal Ilmu Komputer dan Informasi, 2016)
Stuttered speech is a dysfluency rich speech, more prevalent in males than females. It has been associated with insufficient air pressure or poor articulation, even though the root causes are more complex. The primary features include prolonged speech and repetitive speech, while some of its secondary features include, anxiety, fear, and shame. This study used LPC analysis and synthesis algorithms to reconstruct the stuttered speech. The results were evaluated using cepstral distance, Itakura-Saito distance, mean square error, and likelihood ratio. These measures implied perfect speech reconstruction quality. ASR was used for further testing, and the results showed that all the reconstructed speech samples were perfectly recognized while only three samples of the original speech were perfectly recognized.